Big data analytics in telecommunications: Governance, architecture and use cases - Mohamed Zouheir Kastouni; Ayoub Ait Lahcen (Journal of King Saud University. Computer and information sciences, 2022)
With the upsurge of data traffic due to the change in customer behavior towards the use of telecommunications services, fostered by the current global health situation (mainly due to Covid-19), the telecommunications operators have a golden opportunity to create new sources of revenues using Big Data Analytics (BDA) solutions. Looking to setting up a BDA project, we faced several challenges, notably, in terms of choice of the technical solution from the plethora of the existing tools, and the choice of the governance methodologies for governing the project and the data. The majority of research documents related to the telecommunications industry have not addressed BDA project implementation from start to finish. The purpose of this study focuses on a BDA telecommunications project, namely, Project’s Governance, Architecture, Data Governance and the BDA Project’s Team. The last part of this study presents useful BDA use cases, in terms of applications enabling revenue creation and cost optimization. It appears that this work will facilitate the implementation of BDA projects, and enable telecommunications operators to have a better understanding about the fundamental aspects to be focused on. It is therefore, a study that will contribute positively toward such goal.